ISO Technology Analysis with Extended TAM : A Case Study in PT Ebako Nusantara - Hutagaol, Nindhia; Pasaribu, Faizal Asrul; Simangunsong, Jumadi (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2025)
Implementing information systems in manufacturing aims to improve operational efficiency and service quality. This study evaluates the acceptance of Internal Service Order (ISO) applications with the Extended Technology Acceptance Model (ETAM), that adds variables such as information quality, system quality and user habits. PLS-SEM analysis of 31 respondents found that user habits significantly influenced perceived ease of use (77.8%), which in turn influenced perceived usefulness (86.4%) and user attitude (62%). However, information quality did not significantly influence user habits, suggesting a need to improve information detail. These findings will help develop a TAM model for Indonesian furniture companies. The study recommends the improvement of information accuracy, the development of real-time notification features, and user training to increase adoption and operational efficiency This study provides guidance for organizations to optimize the application of technology in manufacturing operations.